Pendidikan Islam Transformatif (Menggali Karakteristik Manajemen Perubahan Yang Efektif) - Rofik, Zainur (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine the characteristics of transformative Islamic education change management. This research is important because the world of Islamic education is faced with globalization, which demands improvements in the management of Islamic education with character. Four main problems were found: (1) what is meant by change management, (2) what is the difference between general and Islamic change management, (3) what are the characteristics of change management in Islamic education, (4) what are examples of its application in facing the global era. Through a qualitative descriptive approach in the form of a literature review, namely by collecting data such as books and journals and analyzing it using content analysis, the research produced findings that the process of creating a sustainable learning culture in organizations is to increase the ability to adapt to change. The difference between general change management and change management in Islamic educational institutions lies in the basis used. General change management is based on the philosophy of naturalism, while Islamic education change management is based on the Koran and the Sunnah of the Prophet. The character is also different, the management of Islamic education is more towards anthropocentric theory. An example of its application is by applying these characters to Islamic education management practices to become transformative Islamic education.